PRINCIPLE OF REHABILITATION & COMPLICATION PREVENTION AFTER MUSCULOSKELETAL TRAUMA - Utomo, Pamudji; Akbar, Hillan (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2021)
Rehabilitation plays a major role to maximize outcome and prevent complications following musculoskeletal trauma and its interventions. It is reported in several studies that mortality risk in patients not receiving rehabilitation was higher compared with patients who received one. The key principles include adequate pain management, anti-infection measures, early ambulation and physical therapy, establishing proper milestones and goals, well-communicated multi-disciplinary approach, and the establishment of standardized and personalized treatment protocol. Early mobilization is supported, as long as wound healing has been taken into consideration. Holistic approach to ensure both physical and psychosocial well-being is recommended, along with special care for geriatric and paediatric populations. Furthermore, alternative medicines such as acupuncture and meditation are currently gaining popularity and subsequently advocated as adjunct therapies.